APLIKASI PENDISTRIBUSIAN MATERIAL PADA WAREHOUSE BERBASIS WEB MENGGUNAKAN ALGORITMA APRIORI (STUDI KASUS PT. TELKOM AKSES WITEL BANTEN) - Try Rahmanda Putra (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
A warehouse is a place to store goods in a company. Almost all business sectors, be it industry, culinary, and even network infrastructure development require warehousing in running their business. Warehouses in companies engaged in network infrastructure development usually contain poles, pole accessories, patch cable cords, optical distribution points (ODP), underground distribution cables, air distribution cables, and passive splitters. Apriori algorithms are basic algorithms proposed by Agrawal and Srikant in 1994 for the determination of frequent itemsets for Boolean association rules.The main idea of a priori algorithms is to first find sets of items that meet the minimum support (frequent itemset) from the transaction database, secondly eliminate items with low frequency based on predetermined minimum support levels. Next build an association rule from an itemset that meets the minimum confidence value in the database. This application is designed to simplify and speed up colleagues or partners regarding material distribution, made this application with a mysql database with 4 entities and 24 attributes and relationships between entities using ERD. The application is designed using apriori algorithm that contains data from the results of goods that have been removed from the outgoing goods table. Keywords : Material distribution application, a priori algorithm, MySQL database xiii+61 pages; 38 images; 20 tables; Reference list: 8 (2018-2022)